Respuestas

2013-01-04T02:46:01+01:00

Solamente operas:

 x+1/x-1 + x-2/x+2 = 3

 

(x+1)(x+2)+(x-1)(x-2)/(x-1)(x+2)=3

(x+1)(x+2)+(x-1)(x-2)=3(x-1)(x+2)

x^2+3x+2+x^2-3x+2=3(x^2+x-2)

2x^2+4=3x^2+3x-6

0=x^2+3x-10

     x           +5

     x            -2

0=(x+5)(x-2)

Entonces "X" puede ser:  x=-5     y   x=2

SALUDOS

2013-01-04T02:52:25+01:00

x+1/x-1 + x-2/x+2 = 3

(x+1)(x+2)+(x-2)(x-1)= 3(x+2)(x-1)

(x^{2}+3x+2 )+(x^{2}-3x+2 )= 3(x^{2}+x-2 )

2x^{2}+4=3x^{2}+3x-6

 [x^{2}+3x-10=0

ahora necesitamos 2 # k multiplicados nos den 10 y restados 3

(x+5)(x-2)=0

las respustas serian 

x+5=0 -----------> x=-5

x-2=0------------>x=2

espero que te sirva